Firm growth and firm value: Moderation role of board size during Russia-Ukraine war - Sari, AA Pt Agung Mirah Purnama; Tjahjadi, Bambang (International Journal of Management and Sustainability, 2024)
This study’s objective is to investigate the influence of board size as a moderator in a research model examining the impact of firm growth on firm value, considering the impact of the Russia-Ukraine war on Indonesia over the past seven years. The study consisted of 328 observations, ranging from 2014 to 2021. This study discovered that company expansion has a considerable beneficial impact on firm value. The board of directors has the ability to operate as a moderating variable, whereas the board of commissioners did not moderate the impact of firm expansion on company value. The results of the research aligned with the signaling theory, which posited that a company’s ability to expand is a crucial indicator of its success. The market responded positively to this positive signal, drawing in new investors who subsequently increased the company’s value. This study revealed that, despite their important functions in a company, the board of directors and the boards of commissioners were unable to mitigate the impact of firm expansion on firm value. This could be caused by external factors like the Indonesian economy and market during the Russia-Ukraine conflict. The Russia-Ukraine war affected Indonesian companies, but they remained stable until now. The researcher was unable to acquire financial data from non-public firms impacted by the conflict between Russia and Ukraine, resulting in a small sample size.